Research in the field of vibration of automotive systems. Issue 1 (July 2020) - Stanescu, M; Ionica, V; Geonea, I; Miritoiu, C; Bolcu, A
Abstract: The aim of the research is to improve knowledge about the behaviour of materials and structures, to develop models and tools useful in the process of design of structures and machines and to capitalize on a technical culture in terms of analysis, design and manufacturing methodologies. We also set out to show the influence of which types of vibrations have an effect on the operation of the crankshaft mechanism of a car engine, as well as their influence on the operation of the camshaft system, all of which are taken into account in any design process in this field. The generalization of the theory of elasticity and the dynamics of viscous fluids led to the creation of the linear theory of viscos-elasticity, the bodies with such a behaviour obeying the principle of overlapping Boltzmann. Thus, mechanical models were built consisting of spring and damping systems, the springs describing the elastic properties of the body, and the dampers on the viscous ones.